Revise and Re-evaluate Cross Cultural Understanding Curriculum at Akademi Bahasa Asing Balikpapan (Foriegn Language Academy of Balikpapan) - Rachmi Sari Baso (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
The study is about the project to revise and re-evaluate the unit of Cross Cultural Understanding curriculum which is taught in the Akademi Bahasa Asing Ballikpapan. The unit is for fifth semester students. The project aimed to provide students' perspectives of cross cultural differences in the workplace with the materials and knowledge that suitable for workplace demands. The information was gained by distributing questionnaires to 2 teachers and 2 employers of multinational companies in Balikpapan. The investigations for teachers were focused on the content, learning activities and materials of the current curriculum. The investigations for the employers were focused on their perspectives on the cross cultural understanding taught in the higher education. The project used Nicholls' cycle model that will be a useful tool to regularly evaluate curriculum based on the situational analysis. As the result, there were some of materials of American business cultural encounter should be revised to meet the companies demands and additional table manners in cultural perspectives should be included in the curriculum. Therefore, the new curriculum will be applied by these materials as the demands of the workplace.